In sickness and in health: The role of housework engagement in work productivity despite presenteeism - Correia Leal, C.; Ferreira, A. I. (The Spanish Journal of Psychology, 2021)
The present study is one of the first to investigate the effects of housework engagement on work productivity despite sickness presenteeism and to explore personality traits (i.e., conscientiousness) and gender differences among couples. Based on a sample of 180 heterosexual couples, an integrated model of both housework and workplace realities was proposed and tested based on the actor-partner interdependence model using structural equation modeling. The results verify that the higher the degree of women's conscientiousness, the greater their and their partners' level of productivity despite presenteeism. In addition, the higher the couple's perception of partner support is, the greater their level of work productivity despite health problems, for both men and women. Results also confirm that housework engagement mediates the relationships between both conscientiousness and perceived partner support and work productivity despite health problems, for women, but not for men. This study denotes an advance in the literature on the relationships between personal and social resources within the family domain and work productivity despite sickness presenteeism. The findings support the applicability of the resource perspective of the Job Demands-Resources theory (JD-R) (i.e., motivational branch) to housework, as well as extend existing presenteeism models by providing evidence for the inclusion of the family domain in explaining this organizational phenomenon.